2006
DOI: 10.1007/s00198-006-0243-6
|View full text |Cite
|
Sign up to set email alerts
|

Height and bone mineral density in androgen insensitivity syndrome with mutations in the androgen receptor gene

Abstract: Subjects with AIS had mean final height intermediate between mean normal male and female, and decreased bone mineral density in the lumbar spine. These data suggest an important role for androgens in normal male growth and bone density not replaced by estrogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 35 publications
3
76
0
Order By: Relevance
“…The findings of greater BMD at the hip than at the spine in CAIS women in the present study are consistent with those observed by Danilovic et al in a study of complete and partial AIS women (22). The long-term effects of androgens on BMD in free-living subjects have not been demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of greater BMD at the hip than at the spine in CAIS women in the present study are consistent with those observed by Danilovic et al in a study of complete and partial AIS women (22). The long-term effects of androgens on BMD in free-living subjects have not been demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…However, it has been established, at least in rodents, that androgen action on bone can be directly mediated by activation of AR in the absence of ER [30,31]. In addition, findings from individuals with androgen insensitivity syndrome suggest that androgens play an important role in normal male growth and maintenance of bone density which cannot be filled by estrogens [32,33].On the other hand, a recent clinical review concerning the impact of T therapy on bone health [34] concluded that the available trials do not provide convincing evidence for the efficacy of T in preventing and treating osteoporosis, and that further data on fractures need to be accumulated. As for the impact of 19-norandrogens on bone, MENT prevented the decreases in cortical and trabecular bone mineral density associated with orchidectomy in aged male rats [35], whereas effects of DMA and 11β-MNT on bone mineral density have yet to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is commonly reported, however, at rates that mimic the general population of women [10, 21]. Decreased bone mineral densities in the lumbar spine and hip regions occur both prior to gonadectomy in women with CAIS as well as in gonadectomized women receiving daily estrogen therapy [10, 21, 22].…”
Section: Androgen Insensitivity Syndromes (Aiss)mentioning
confidence: 99%